Role of on-screen visual stimuli reaction times, subcomponents of attention, and gender in RAN and reading fluency association. - Karantinou, Evgenia (2021)
Rapid automatized naming (RAN) is the capacity to retrieve and fluently designate serially displayed stimuli, e.g. letters or objects. RAN, as a speeded task, is correlated with processing speed and reaction times. RAN is a strong predictor of reading skills in transparent orthographies and it has been found that this association might be due to underlying attentional processes. The Attention Network experiment (ANT) is the most common experiment obtained for measuring the three subcomponents of attention (alerting, orienting, inhibition). The purpose of this study is to examine whether the reaction times in different visual stimuli and the subcomponents of attention predict RAN performance as well as whether they moderate the relationship between RAN and reading fluency. This study obtains psychometric data from the eSeek project and an ANT experiment conducted by Santhana Gopalan (2019; 2020). 166 participants completed the psychometric tests and 115 of those participated in the ANT experiment. Analysis was conducted using SPSS 26 and Pearson’s correlations, hierarchical regression and moderation analysis were used to answer the research questions. This study showed that RAN predicts reading fluency and that gender acts as a moderator in the relationship between RAN and reading fluency. Reaction times were a significant predictor of RAN performance in both the letters and the objects tasks and moderated RAN performance in objects, together with gender. Orienting was found to predict and moderate RAN performance in the letters task. Alerting and inhibition were a significant predictor of RAN performance in objects. The main results managed to clarify the connection between reading fluency, RAN performance, reaction times and the subcomponents of attention. As this topic has not been investigated before, it provided new insight in this matter.